Izdelava registra plus dreves divje češnje (Prunus avium L.) v Sloveniji - Jarni, Kristjan (Gozdarski vestnik, 2017)
Wild cherry (Prunus avium L.) is an increasingly important minority tree species due to its ecological significance and quality wood, but it is difficult to ensure sufficient amounts of quality forest reproductive material for this species. With the help of the Slovenia Forest Service we recorded 127 candidates for wild cherry plus trees in the entire area of Slovenia. More detailed evaluation of these trees resulted in the selection of 107 trees of the most desirable characteristics to be included into the registry of wild cherry plus trees. These trees will be used for establishing a wild cherry breeding program and seed orchard, which will enable the production of sufficient amounts of genetically improved forest reproductive material. The register will also serve as an example for other minority tree species.
Keywords: divja češnja; Prunus avium L.; wild cherry; plus drevesa; plus trees; seed orchard; semenska plantaža; forest reproductive material; gozdni reprodukcijski material; žlahtnjenje gozdnega drevja; tree breeding; Slovenia; Slovenija